Latin American Lending by Major U. S. Banks: The Effects of Disclosures about Nonaccrual Loans and Loan Loss Provisions - Griffin, Paul A.; Samoa J. R. Wallach (The Accounting Review, 1991)
[During 1987, the climate of international bank lending changed dramatically and prompted major restatements of the loan portfolios of the largest U.S. money-center and regional banks. The circumstances involved decisions by several countries in Latin America-notably Brazil-to suspend scheduled interest and principal payments on their foreign debt. The exposure of the U.S. banks became most visible on February 20, 1987, when Brazil declared a moratorium on interest payments on 67 billion of medium- and long-term bank debt and, five days later, froze payments on 10 billion of short-term credits and $5 billion of money market deposits. A chain of events began in March 1987 and produced the largest reported losses in U.S. banking history. This article examines how the stockholders' returns of 13 of the largest U.S. money-center and regional banks were affected by disclosures made during 1987 regarding decisions to place Brazilian loans on a nonaccrual basis and to increase loan loss reserves to recognize the higher probability of default and the lower present value of future interest and principal. The study adds to the recent literature on banks' earnings and asset relations (Barth et al. 1990; Beaver et al. 1989) and to the accumulated evidence on the role of banks' accounting decisions in response to the resulting substantial asset impairment caused by the 1987 Latin American debt situation (Elliott et al. 1989; Grammatikos and Saunders 1990; Johnson 1989; Musumeci and Sinkey 1990a, 1990b). Using a methodology that focuses on the unanticipated short-term effects of the announcements, we find that the stock market responded adversely to the banks' reclassification of loans to the nonaccrual basis and positively to subsequent announcements of additions to loan loss provisions. The latter reaction is viewed as consistent with banks' use of those adjustments as credible signals about their intentions and abilities to resolve the Latin American debt situation. We also find that changes in secondary market prices for Brazilian loans explain banks' stockholders returns during the period and that returns measured over short intervals varied according to the balance-sheet amount of foreign loans. Such results are consistent with the hypothesis that the stock market discriminates among banks on the basis of reported foreign loan data.]